Reviving mB. Issue 3 (30th November 2018) - Kanamori, Hiroo; Ross, Zachary E
SUMMARY: We determine m B, the original body wave magnitude developed by Gutenberg and Richter over the period 1942–1956, for about 3300 M w ≥ 6 earthquakes for the period 1988–present using modern broad-band seismograms. The main objective is to extend the database of energy-related parameters by combining m B databases for recent and old events. The radiated energy E R_B (in erg) computed from m B using the Gutenberg & Richter relation $\log {E_{ R_ B}} = 2.4{m_ B} + 5.8$ agrees very well with E R estimated with modern techniques, especially for large deep earthquakes. Thus, E R_B is useful as a proxy for E R to investigate the global diversity of earthquake characteristics and physics over an extended period of time.